1996
DOI: 10.1021/jf950502+
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nicotine Extraction from Tobacco Using Supercritical Fluid Technology with Dynamic Extraction Modeling

Abstract: The influence of particle size, cell geometry, and packing of the extraction cell was investigated for the extraction of nicotine from tobacco using supercritical CO2 modified with methanol using the hot-ball model of Bartle et al. (1990). When the tobacco was powdered to a particle size of 125−355 μm, the optimum extraction time was reduced by 15 min. Within this particle size range, particle size did not influence the recovery of nicotine so that a time-consuming sieving step is not required. The presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…In the past decade, supercritical fluids have been used for extraction of different components from tobacco and tobacco byproducts. For example, methanol-modified carbon dioxide has been used to remove nicotine from tobacco (8). The same fluid was also used to quantitatively remove N-nitrosamines from both smokeless tobacco and cigarettes (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, supercritical fluids have been used for extraction of different components from tobacco and tobacco byproducts. For example, methanol-modified carbon dioxide has been used to remove nicotine from tobacco (8). The same fluid was also used to quantitatively remove N-nitrosamines from both smokeless tobacco and cigarettes (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The SC CO 2 extraction has been used for removing nicotine [ 20 ]. It was proposed that the moisture and compounds present in plant material influence the extraction yield of nicotine [ 13 ]. The results obtained indicated that the pressure has a significant influence on nicotine yield [ 11 , 14 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mixture of tobacco varieties, in form of 32.5% flue-cured, 19.9% Burley, 1.2% Maryland, 11.1% Oriental and 27.1% reconstituted, has been used for the SC CO 2 extraction of nicotine under the pressure of 26 MPa and temperature of 70 °C [ 10 ]. The influence of particle size, cell geometry and packing of the extraction cell was investigated for the extraction of nicotine from the tobacco using cosolvent, 12 cm 3 MeOH:41.2 mM KH 2 PO 4 = 2:3, under the pressure of 13.7 MPa, temperature of 100 °C for 35 min [ 13 ]. Tobacco waste, derived from tobacco leaves and obtained during tobacco processing, has been used for the extraction of nicotine by SC CO 2 extraction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, alkaloids are important for different areas of the economy, industry, trade, and services and can be used in some applications as well as agricultural insecticide or health medicines. , The nicotine detection in trace levels is crucial, considering its addictive property . Meanwhile, caffeine plays an important role in the medical field and sports science, and food engineering. , Common methods used for extraction of these alkaloids, such as supercritical carbon dioxide, liquid–liquid and solid–liquid extraction with organic solvents, present low extraction yields. Besides, these methods can generate undesirable compounds, in addition to using toxic organic solvents …”
Section: Introductionmentioning
confidence: 99%